Analysis of Power Loss for Crystalline Silicon Solar Module during the Course of Encapsulation - Hong Yang; He Wang; Dingyue Cao; Dangmin Sun; Xiaobao Ju (International Journal of Photoenergy)
During the course of solar module encapsulation, the output power of crystalline silicon solar module is less than the sum of the maximum output power of the constituents because of power loss. So it is very important to investigate the power loss caused by encapsulation materials and module production process. In this paper, the power loss of crystalline silicon solar module is investigated by experiments systematically for the first time. It is found that the power loss is mainly caused by the resistance of ribbon and mismatch of solar cells; the total power loss is as high as 3.93% for solar module composed of 72 cells (125 mm × 125 mm) connected in series. Analyzing and reducing the power losses are beneficial to optimizing encapsulation process for the solar module. The results presented in this study give out a direction to decreasing power loss and optimizing encapsulation process of crystalline silicon solar module.